Análisis de las políticas públicas y su incidencia en la violencia de género en la ruralidad norte del cantón Chone - Loor Cedeño, Melissa Nereida (2024)
The objective of this research was to analyze the public policies, programs and projects implemented by the Municipal and Parochiales Decentralized Autonomous Government in Chone cantón for the prevention and eradication of gender violence. The study was carried out through inductive, deductive, analytical and synthetic methods, using interview and survey techniques. Data collection was carried out using the Likert scale, and bibliographic, field and descriptive research types were used. The development of this work was divided into three stages. In the first stage, the established regulations that promote and contribute to the eradication of gender violence in the northern rural area in Chone canton were identified, through bibliographic research and documentary review. In the second stage, interviews were carried out with the presidents of each Parish GAD and the political lieutenant of the parish, in addition, a survey was applied to the citizens to collect information and compare it in order to meet the proposed objectives. In the third stage, a strategy plan was proposed that includes improvement actions and possible solutions to contribute to the population of the rural areas mentioned above. With the development of the research, main problems were identified such as ignorance, demotivation, and lack of empathy on the part of rural citizens, in addition to the lack of public policies that contribute to this social problem.